2018
DOI: 10.18502/kss.v3i3.1889
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tourist Attractions Towards the Tourists’ Satisfaction

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Domestic tourists who visited earlier some tourist spots in Bangladesh and stayed hotels and motels at least one night were included as samples. Therefore, Kirom and Putra (2018) and Figure 2.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Domestic tourists who visited earlier some tourist spots in Bangladesh and stayed hotels and motels at least one night were included as samples. Therefore, Kirom and Putra (2018) and Figure 2.…”
Section: Methodsmentioning
confidence: 96%
“…Domestic tourists who visited earlier some tourist spots in Bangladesh and stayed hotels and motels at least one night were included as samples. Therefore, Kirom and Putra (2018) and Bhat and Darzi (2018) collected data adopting the purposive sampling method for measuring tourist satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies (e.g., Boit & Doh, 2014;Kirom et al, 2018) revealed that culture has positive and significant impact towards tourists' satisfaction. Subsequently, the attribute regarding a cultural destination demonstrated positive impression on the satisfaction of tourists visiting that specific destination (Putri, 2017).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Over the past decades, tourism carries its role which the local economy is beneficiary of its positive impression (Carmignani & Moyle, 2019). Generally, attractions related to tourism are regarded as the pull factor that attract tourists to go to a certain place or area where the attractions must be well-developed (Kirom et al, 2018). Thus, a destination can hardly be called as an object of tourism if there is an absence of attractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation